Assessing the Impact of Haulage Drivers in Uganda's COVID-19 Delta Wave - Adrian Muwonge; Paul R. Bessell; Mark Barend de Clare Bronsvoort; Ibrahim Mugerwa; Erisa Mwaka; Emmanuel Ssebaggala; Bryan Aidan Wee; Aggelos Kiayias; Christine Mbabazi Mpyangu; Moses Lutakome Joloba (Journal of Epidemiology and Global Health)
Abstract Background Haulage truck drivers connect distant communities, posing potential disease introduction risks. However, interventions must balance public health protection, economic continuity, and individual rights. This study examines the role of haulage in disease introduction and onward spread in Uganda during the Delta wave of COVID-19. Methods Using 625,422 national surveillance records, we fitted a susceptible-infectious-recovered model to assess whether haulage drivers were a “core-risk group.” Although they accounted for only 0.036% of COVID-19 cases, border districts associated with haulage registered 12.02% more cases than inland districts, suggesting a role in disease introduction. The risk varied by location, with Tororo experiencing a higher burden than Amuru and Kyotera, which border South Sudan and Tanzania, respectively. Mandatory COVID-19 testing and result waiting at the Malaba border crossing increased disease risk in Tororo by up to 6%. While haulage-targeted interventions reduced cases in border districts, they had minimal impact on inland districts, indicating a limited role in onward spread. Our findings also suggest that integrating haulage-specific measures with vaccination would further reduce case-load. Conclusions Our findings suggest that truck drivers were a transient core risk group with limited impact on onward spread. However, uncertainties remain regarding the extent of their role, and interventions like testing and result waiting at border crossings may have inadvertently heightened risk. Pandemic preparedness strategies should carefully assess risks in key sectors like supply chains to balance public safety with individual rights.